Premarital Screening: A Catalyst for Achieving Good Health and Well-Being - Sidabutar, Nadya Hanna Talitha; Ella Nurlaella Hadi (Universitas Airlangga, 2024)
Background: Premarital screening is a comprehensive examination that must be done before marriage, which includes examinations of reproductive organs, genetic diseases, infectious diseases, and blood-borne infections. The screening aims to avoid the risk of long-term diseases for couples and their descendants. This screening can also prevent maternal and infant mortality, birth defects, and stunting because risk factors can be detected and addressed early in the mother and baby-to-be. Despite its importance, premarital screening behavior is not culturally embedded. Aims: This study aimed to determine factors associated with premarital screening behavior. Methods: This research uses systematic review as its design from Google Scholar and Scopus databases that discuss the determinants of premarital screening behavior with quantitative methods. Articles were collected with the keywords